Faktor Risiko Yang Berhubungan Dengan Kejadian Ikterus Neonatorum Pada Bayi Baru Lahir - Rully Fatriani (LPPM STIKes Panca Bhakti Bandar Lampung, 2020)
Neonatal jaundice is a health problem that is often found among newborns in the first week of life, if not treated early can be fatal and even death. This study aims to determine the risk factors associated with the incidence of neonatal jaundice in newborns. This correlative analytic study with cross sectional approach was conducted on 188 newborns, taken by systematic random sampling. Data obtained from medical records and analyzed using chi-square test. The results showed 82 (43.6%) newborns had neonatal jaundice, with 42 (71.2%) newborns from 59 newborns with a history of oxytocin-induced labor had neonatal jaundice , 24 (68,6%) newborns from 35 premature newborns had neonatal jaundice and 48 (35,3%) newborns from 136 breastfed newborns had neonatal jaundice. The conclusion of this study is that neonatal jaundice is more likely to occur in newborns with a history of oxytocin-induced labor, premature newborns and newborns who are breastfed. Authorized health workers are expected to minimize the actions of oxytocin induction and carry out intensive care according to procedures in newborns.